Ira A. Nadeau, Director General, giving a speech on Stockholders Day, Alaska-Yukon-Pacific Exposition, Seattle, Washington, September 19, 1908 - Nowell, Frank H., 1864-1950 (1908)
PH Coll 727.11 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number